Avaliação de durabilidade de concretos com substituição parcial do cimento Portland pela cinza da folha de bananeira - Marques, Tiago Rocha (Universidade Federal Rural do Semi-Árido, 2019)
In the current perspective of the civil construction the search for alternative and natural materials that make possible the constructive processes becomes essential for study, mainly for the concretes that are attributed to many constructions in the world. In this study we have highlighted the ashes of the banana leaf that after the burning and milling is expected pozolânica characteristics in the incorporation in concretes. The objective of this work is to analyze aspects of concrete durability with the partial substitution of the ashes of the banana leaf in the parameters of carbonation and ultrasound. For the study in question, 6 test specimens with different contents of 0%, 5% and 10% of material applied to the concretes were produced, then these specimens were exposed to the environment for the study of carbonation at the ages of 30 and 60 days and for a study of propagation of ultrasonic waves after the 60 days of the concrete produced, finally the depth of penetration of CO2 with phenolphthalein was observed. For the concretes produced with residues a reduction in the carbonation depth was observed with the increase in the substitution content. The mixture with 10% ash had a depth of 4.7 mm lower than the reference concrete, obtaining a reduction of 54.29% in the concrete carbonation depth. This fact due to the reduction in the porosity of these composites and increase in ultrasonic pulse propagation velocities, being this velocity of 4189.94 m / s for T10%, presents the best characteristics in the incorporation process, containing an increase of 6.14 % in velocity relative to the reference concrete, obtaining significant results regarding the application of the ashes of the banana leaf for the production of concrete indicates a more durable concrete.
Keywords: Ultrassom; Carbonatação; Resíduos da Biomassa; Ultrasound; Carbonation; Biomass residues; ENGENHARIAS::ENGENHARIA CIVIL